2017
DOI: 10.2147/cmar.s100210
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of malignant ascites: patient selection and perspectives

Abstract: Malignant ascites (MA) is a sign of advanced cancer and poor prognosis. MA can result in impairment in quality of life (QOL) and significant symptoms. As a supportive treatment, ascites can be drained by paracentesis (PC), percutaneously implanted catheters (tunneled, untunneled, central venous catheters), or peritoneal ports, or peritoneovenous shunts. The aim of this study was to evaluate the effectiveness, safety, and patient-reported outcomes (PRO) of different drainage methods for the management of MA. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 53 publications
1
69
0
Order By: Relevance
“…However, our databases covered all eligible patients in the participating centres which would minimise selection bias. The baseline demographics of this case series were similar to previously published case series, showing similar age range, female predominance and range of malignancies . Second, the participating centres all had pleural specialists with training and experience in IPC management and a dedicated aftercare support service.…”
Section: Discussionsupporting
confidence: 63%
“…However, our databases covered all eligible patients in the participating centres which would minimise selection bias. The baseline demographics of this case series were similar to previously published case series, showing similar age range, female predominance and range of malignancies . Second, the participating centres all had pleural specialists with training and experience in IPC management and a dedicated aftercare support service.…”
Section: Discussionsupporting
confidence: 63%
“…Low nutritional status and a past history of heart, liver, and renal failure in the patient can also contribute to the presence of ascites. Therefore, the causes of ascites in patients with advanced cancer could be attributed to a number of etiological factors 11) . This suggests that a single cause of ascites does not have significant prognostic value, as multiple factors including low nutrition, cancer cachexia, and organ failure influence the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of supportive treatment, ascites can be drained by paracentesis, percutaneously implanted catheters or peritoneal ports, and peritoneovenous shunts [75]. A systematic review of drainage techniques reported that symptom control was achieved in approximately 97% of patients after ascites drainage and, importantly, PROs and QoL were also improved after drainage [75]. However, drainage of ascites is associated with fatigue and hemodynamic instability [76], thought to be related to the loss of proteins in the drainage fluid.…”
Section: Supportive Treatments For Ascitesmentioning
confidence: 99%